New Frontiers in Stellar Interferometry 2004
DOI: 10.1117/12.551072
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial single-mode beam combiner

Abstract: To achieve high rejection ratios with a nulling interferometer, the beams to be combined have to be as equal as possible, especially concerning the transverse field distribution. This requires highly symmetric beam recombination stages as well as modal wavefront filtering. Usually co-axial beam recombination employing beam splitters is used, ideally in highly symmetrizing double-pass configurations. Considering that a single-mode waveguide is required anyway for spatial wavefront filtering, it seems reasonable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Such a sum can be achieved in an elegant and simple way thanks to a single-mode fiber optics. The efficiency of this cancelling device has actually been demonstrated (e.g., Wallner et al 2004;Buisset et al 2006). To obtain A(−u, v) = A(u, v), and because the sin(πuD) function is odd, it is sufficient to make sure that Sum (e jπPΛ − e jπQΛ ) · expUV(u, v) is even.…”
Section: The Multi-axial Chessboardsmentioning
confidence: 99%
“…Such a sum can be achieved in an elegant and simple way thanks to a single-mode fiber optics. The efficiency of this cancelling device has actually been demonstrated (e.g., Wallner et al 2004;Buisset et al 2006). To obtain A(−u, v) = A(u, v), and because the sin(πuD) function is odd, it is sufficient to make sure that Sum (e jπPΛ − e jπQΛ ) · expUV(u, v) is even.…”
Section: The Multi-axial Chessboardsmentioning
confidence: 99%
“…3. This scheme was first proposed by Wallner et al (2004) and demonstrated experimentally by Haguenauer & Serabyn (2006) and Buisset (2006). We decided to make use of this property due to the simplicity of its implementation.…”
Section: Methodsmentioning
confidence: 99%
“…This filter will affect the field distribution and therefore the rejection ratio. In the case of multi-axial nulling interferometry, an efficient way to perform wavefront filtering is to focus the light from the different beams into a unique single-mode fiber (positioned at the focus of the imaging system) (Mennesson et al 2002;Wallner et al 2004). In this section, we will study the filtering capabilities of a single-mode fiber with respect to the longitudinal polarization issue.…”
Section: Longitudinal Polarization and Single-mode Fibersmentioning
confidence: 99%